Efficient p‐Type Doping of Tin Halide Perovskite via Sequential Diffusion for Thermoelectrics. Issue 6 (6th March 2022) - Chen, Ruisi; Yan, Yajie; Tang, Junhui; Zeng, Huarong; Yao, Qin; Chen, Lidong; Liang, Ziqi
Abstract : Metal halide perovskites (MHPs) hold great potential in thermoelectric (TE) applications, thanks to their regular and soft lattice in nature. However, the poor electrical conductivity caused by low charge carrier density (<10 14  cm −3 for lead‐based MHPs) strongly impedes its TE development. In this scenario, tin halide perovskites (THPs) emerge as promising TE candidates owing to their high background hole densities (>10 19  cm −3 ). However, further electrical doping remains challenging, originating from the limited capability of accommodating heterogeneous dopants and the heavy compensation in THPs. Herein, a novel diffusion‐mediated doping approach is demonstrated to prominently increase the p‐type doping level of THPs by a sequence of air exposure and 2, 3, 5, 6‐tetrafluoro‐7, 7, 8, 8‐tetracyanoquinodimethane (F4 TCNQ) surface treatments. In paradigm photovoltaic THP materials—CH(NH2 )2 SnI3 (namely FASnI3 ), the electrical conductivity is dramatically increased by 300× from 0.06 to 18 S cm −1 in thin films, leading to a remarkable enhancement of power factor by 25× up to 53 μW m −1  K −2 . In contrast, only a slight variation of thermal conductivity is observed after F4 TCNQ deposition, which is in accordance with the increase in electrical conductivity, indicating that the lattice structures of FASnI3 remain intact after doping. This study paves an illuminating way to ameliorate TE properties in halide perovskites. Abstract : A sequential diffusion doping strategy of air exposure and then F4 TCNQ surface treatment is demonstrated in CH(NH2 )2 SnI3 films to achieve a remarkably increased electrical conductivity up to 18 S cm −1, leading to an impressive thermoelectric power factor of 53 μW m −1  K −2 . Such diffusion doping enables effective interactions between heterogenous dopants and CH(NH2 )2 SnI3 lattices, while revealing the underlying distinct doping mechanisms.